Distance from the Belsen heap : allied forces and the liberation of a Nazi concentration camp - Celinscak, Mark 1978- (University of Toronto Press, 2015)
The Allied soldiers who liberated the Nazi concentration camp at Bergen-Belsen in April 1945 were faced with scenes of horror and privation. With breathtaking thoroughness, Distance from the Belsen Heap documents what they saw and how they came to terms with those images over the course of the next seventy years. On the basis of research in more than seventy archives in four countries, Mark Celinscak analyses how these military personnel struggled with the intense experience of the camp; how they attempted to describe what they had seen, heard, and felt to those back home; and how their lives were transformed by that experience. He also brings to light the previously unacknowledged presence of hundreds of Canadians among the camp's liberators, including noted painter Alex Colville. Distance from the Belsen Heap examines the experiences of hundreds of British and Canadian eyewitnesses to atrocity, including war artists, photographers, medical personnel, and chaplains. A study of the complicated encounter between these Allied soldiers and the horrors of the Holocaust, Distance from the Belsen Heap is a testament to their experience.